2005 Cotton Variety Trials in Florida: Mid- and Late-Maturing Cultivars - David L. Wright; C. A. Smith; E. B. Baxley (EDIS)
The cotton variety trials described in this document were planted in conventional tilled soil with a cone planter at the seeding rate of 80 seeds/ 25 linear feet of row with 36” row spacing on May 18, 2005. This document is SS-AGR-34, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date April 2006.